2018
DOI: 10.1097/mnm.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-FDG PET/CT imaging in the staging, restaging, monitoring of response to therapy and surveillance of uterine leiomyosarcomas

Abstract: PET/CT imaging has a high diagnostic yield in the initial staging and restaging of uterine LMS, but seems less sensitive in post-therapy surveillance. Evaluation of the CT part improves the sensitivity of the PET scan. Thus, PET/CT imaging should be considered in patients presenting with LMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Among the radiologic imaging approaches, magnetic resonance imaging (MRI) represents the best approach to imaging of uterine sarcomas, owing to its improved ability to define local spread of disease [15], while computed tomography scan (CT scan) is preferred for staging, assessment of distant metastases and follow-up [16]. Moreover, also the 18-fluoro-D-glucose positron emission tomography ( 18 FDG PET) has been attempted as a diagnostic tool and could eventually be useful; however, current data are limited [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Among the radiologic imaging approaches, magnetic resonance imaging (MRI) represents the best approach to imaging of uterine sarcomas, owing to its improved ability to define local spread of disease [15], while computed tomography scan (CT scan) is preferred for staging, assessment of distant metastases and follow-up [16]. Moreover, also the 18-fluoro-D-glucose positron emission tomography ( 18 FDG PET) has been attempted as a diagnostic tool and could eventually be useful; however, current data are limited [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Roberg et al reported cases of different types of sarcomas, where 10/91 PET negative results of distal metastasis turned out to be incorrect, while CT scans provided reliable data [4]. In a study by Bélissant et al, in 2 described cases of patients with leiomyosarcoma, metastases in the lung and peritoneum were not detected by PET [11]. However, the use of CT alone is not advisable either.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the predominant literature on the subject of preoperative imaging of uterine tumors pertains to MRI, both conventional and functional [5 ▪▪ ,6–9,10 ▪ ,11]. Although the utility of PET in local staging and surveillance for recurrence in leiomyosarcoma has been reported [12,13], its use for differentiating leiomyosarcoma from leiomyoma is less well established, with only a few studies having been reported on the topic [14–18]. Imaging findings for other rarer tumors, such as adenosarcoma, are primarily based on case reports and lack consensus, rendering presurgical diagnosis challenging [19,20].…”
Section: Introductionmentioning
confidence: 99%